CORRELATION BETWEEN C-REACTIVE PROTEIN (CRP) AND BLOOD PRESSURE IN ADULTS - Hanny Siti Nuraeni; Nilam Andini; Chakrawati; Nadia Guntari; Syed Asim Ali Jafary (Hypertension Prevention and Control Research Center, The Polytechnic of Health of Banten, 2026)
C-Reactive Protein (CRP) is a marker of systemic inflammation that increases in chronic inflammatory conditions. Several studies have shown that elevated CRP levels are associated with impaired endothelial function and an increased risk of hypertension. However, the relationship between CRP levels and blood pressure in the adult population still shows varying results. This study aims to determine the correlation between serum CRP levels and blood pressure in adults. This study used a cross-sectional design with a sample size of 30 adult respondents aged 27–60 years who were selected purposively. CRP levels were examined using the Latex Agglutiation method, while blood pressure was measured using a digital sphygmomanometer. Data analysis used Spearman correlation test to determine the relationship between CRP levels and systolic and diastolic blood pressure. The mean CRP levels in respondents were 21 ± 25 mg/L. Statistical analysis showed a significant positive correlation between CRP levels and systolic blood pressure (r = 0.386; p 0.007< 0.05) and diastolic blood pressure (r = -0,048.; p=0,736 > 0.05). Respondents with high CRP levels (>6 mg/L) tended to have higher blood pressure than the group with normal CRP levels. There was a significant positive correlation between CRP levels and systolic blood pressure in adults but no significant correlatrion between CRP levels and diastolic blood pressure in adults. These results indicate that elevated CRP levels can be an early risk indicator for increased blood pressure and potential hypertension. CRP examination can be considered as an additional biomarker in the evaluation of cardiovascular risk.